An Innovative Approach to Hair Regeneration: Synergistic Effects of Zauber™ Hair Drops and Zauberöl® Premium Hair Oil in Testosterone Induced Alopecia Rat Model (Advancements in Homeopathic Research, 2024)
Introduction: Hair loss, or alopecia, is a prevalent concern with  medical and cosmetic implications. Hair loss,  attributed to genetic predisposition, hormonal  imbalances, and psychosocial impacts, necessitates  effective treatments. This study aims to assess the  safety and efficacy of specific formulations Zauber™  Hair Drops (Zauber™) and Zauberöl® Premium  Hair Oil (Zauberöl®) in addressing testosterone induced alopecia, utilizing a rat model. This research  contributes to our understanding of potential solutions  to the rising prevalence of this condition.Materials and Methods: 60 Male Wistar rats were divided into ten groups.  To induce alopecia, testosterone was administered  intramuscularly, excluding the normal control group.  Experimental groups received distinct treatments,  including oral homeopathic drops Zauber™ in mild,  moderate and high doses, topical treatment Zauberöl®  alone and along with ZauberTM in 3 different doses,  and a standard drug, over 28 days. Comprehensive  observations and assessments were conducted. Results and Discussion: The results of the study showed that all groups  maintained their body weights and food consumption,  but those taking Zauber™ and Zauberöl® saw  considerable hair follicle growth without severe  blood clotting or systemic toxicity, as seen by stable  organ weights. The treatment groups showed steady  haematological parameters, and sophisticated imaging  showed that Zauber™ + Zauberöl® effectively  promotes hair follicle growth and development.  Higher anagen-to-telogen ratios in treated groups,  particularly in the Zauber™ + Zauberöl® groups,  show desirable efficiency in alopecia treatment than  the standalone therapies.  Conclusion: Our study highlights the synergistic therapeutic  effects of Zauber™ and Zauberöl® in treating  testosterone-induced alopecia in rats, surpassing  stand-alone therapies. The observed improvements  in various health indicators underscore the  potential efficacy and safety of this combined  treatment approach.
Keywords: Alopecia; Zauber™; Zauberöl®; testosterone-induced alopecia; rat model; efficacy; safety; hair follicle growth